1999
DOI: 10.1063/1.369716
|View full text |Cite
|
Sign up to set email alerts
|

Infrared attenuated total reflection spectroscopy of 6H–SiC(0001) and (0001̄) surfaces

Abstract: Fourier-transformed infrared attenuated total reflection (FTIR–ATR) spectroscopy was used to study the adsorbates on 6H–SiC(0001) and (0001̄) surfaces after chemical treatments and after heat treatments in hydrogen. We obtained clear absorption bands attributable to hydrides and oxides on the SiC surfaces. The ATR spectroscopy revealed polarity dependencies of Si–H and C–H stretch modes between the 6H–SiC(0001) and (0001̄). The surface Si–H bonds on 6H–SiC(0001) formed by the heat treatment in hydrogen were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 30 publications
5
41
0
Order By: Relevance
“…Figure 1 displays spectra of the Si-H and the C-H stretch modes measured on 6H-SiC(0001) and 6H-SiC(0001 ), respectively. The C-H stretch mode on SiC(0001 ) is located at (2851.5 Ϯ0.2) cm Ϫ1 , in good agreement with Tsuchida et al [38][39][40][41] On SiC͑0001͒, two Si-H stretch modes are observed at (2128.0Ϯ0.6) cm Ϫ1 and (2133.5Ϯ0.6) cm Ϫ1 , respectively. The splitting of the Si-H stretch mode, which has also been reported by Tsuchida et al, [38][39][40][41] has been a subject of a detailed study 45 and was shown to be due to a small difference in the third-neighbor interactions of the Si-H dipole with the underlying lattice, which are different for Si-H units on cubic and hexagonally terminated terraces.…”
Section: H-sicˆ0001‰ Surfacessupporting
confidence: 75%
See 1 more Smart Citation
“…Figure 1 displays spectra of the Si-H and the C-H stretch modes measured on 6H-SiC(0001) and 6H-SiC(0001 ), respectively. The C-H stretch mode on SiC(0001 ) is located at (2851.5 Ϯ0.2) cm Ϫ1 , in good agreement with Tsuchida et al [38][39][40][41] On SiC͑0001͒, two Si-H stretch modes are observed at (2128.0Ϯ0.6) cm Ϫ1 and (2133.5Ϯ0.6) cm Ϫ1 , respectively. The splitting of the Si-H stretch mode, which has also been reported by Tsuchida et al, [38][39][40][41] has been a subject of a detailed study 45 and was shown to be due to a small difference in the third-neighbor interactions of the Si-H dipole with the underlying lattice, which are different for Si-H units on cubic and hexagonally terminated terraces.…”
Section: H-sicˆ0001‰ Surfacessupporting
confidence: 75%
“…The wet-chemical procedure also fails for the (0001 ) surfaces for similar reasons. 32,37 The only method to yield SiC͕0001͖ surfaces saturated with a monolayer of hydrogen was first suggested by Tsuchida et al, [38][39][40][41] who have annealed their samples in an atmosphere of ultraclean hydrogen at temperatures of 1000°C and higher. This procedure is similar to the hydrogen etching which is widely used to reduce surface roughness and polishing damage of SiC substrate surfaces prior to homoepitaxial growth by chemical vapor deposition ͑CVD͒.…”
Section: Introductionmentioning
confidence: 99%
“…This process was carried out in a quartz-glass reactor in an atmosphere of palladium-purified ultra-pure molecular hydrogen, similar to the technique used for hydrogen etching [43,44] and hydrogen passivation [45,46,47] of SiC surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…This method was first suggested by Tsuchida and co-workers. [33][34][35][36] We have adopted this method and have studied the chemical, structural and electronic properties of hydrogenated 6H-SiC͕0001͖ surfaces. [37][38][39][40][41][42][43][44][45] The surfaces prepared in this way are free of unwanted contaminants, unreconstructed, chemically inert, and-within certain limits-electronically passivated.…”
Section: Introductionmentioning
confidence: 99%